Mathematical modeling of gas flow in plasma torch vortex chamber - Butyrev, A.E.; Galanin, M.P.; Pereslavtsev, A.V. (Вопросы атомной науки и техники, 2008)
Mathematical model of moving gas in vortex chamber (inter-electrode gas supply insert) of plasma torch channel was developed. Effect of moving electric arc on the motion of gas is considered. Software for solving problems of three dimensional non-ideal gas dynamics in complex areas was developed. Побудовано математичну модель руху газу у форсунці (міжелектродній вставці) і в області анода каналу плазматрона. Модель враховує вплив електричної дуги на течію газу. Розроблено програмний комплекс для рішення завдань тривимірної неідеальної газової динаміки в областях складної геометричної форми. Построена математическая модель движения газа в форсунке (межэлектродной вставке) и в области анода канала плазматрона. Модель учитывает влияние электрической дуги на течение газа. Разработан программный комплекс для решения задач трехмерной неидеальной газовой динамики в областях сложной геометрической формы.